Planning organization and productivity simulation tool for maritime container terminals - Beškovnik, Bojan; Twrdy, Elen (Transport, 2010)
The article describes a proposed planning organization and productivity simulation tool, with a special emphasis on orientations to the optimization of operations in a maritime container terminal. With the application of an adequate model frame for traffic and technical‐technologic forecasting, infrastructure and manpower planning and productivity simulation are possible to measure and increase the productivity in the whole subsystem of the maritime container terminal. The emphasis is mainly put on setting up planning organization in order to collect important information and consequently to raise productivity. This is the main task and goal of terminal management that must develop elements and strategies for optimal operational and financial production. An adequate planning structure must use simplified but efficient simulation tools enabling owners and management to take a vast number of adequate financial and operational decisions. Considering all important and very dynamic facts in container and shipping industry, the proposed simulation tool gives a helpful instrument for checking productivity and its time variation and monitoring a competitive position of a certain maritime terminal with the terminals from the same group. Therefore, the management of every maritime container terminal must establish an appropriate internal planning system as a mechanism for strategic decision support relating basically to the assessment of the best development and optimization solutions for the infrastructure and suprastructure of the entire system. First published online: 10 Feb 2011